Food waste measurement in Australian hospitals and residential aged care homes - Cook, Nathan; Sansome, Kate; Bartrim, Karly; Collins, Jorja (Frontiers in Nutrition, 2025)
Food waste in Australian hospitals and Residential Aged Care Homes (RACH) poses a significant challenge to building a national sustainable food system. These settings generate substantial amounts of food waste due to the complex interaction between patient and resident needs, foodservice operations, staff behaviour and attitudes, food safety regulations and nutrition policies. Measuring food waste is essential to establish baseline waste metrics, guide targeted reduction strategies and evaluate the success of waste reduction efforts in meeting Australia’s national strategy to halve food waste by 2030. Integrating food waste measurement in hospitals and RACH can reduce waste and provide positive environmental and financial outcomes. However, measurement practices in these settings currently use labour-intensive methods, often lacking digital integration, and are conducted ad-hoc as quality improvement activities. Overarching hospital and RACH policy in Australia governing the quality of food and nutrition care is improving and may support further enhancements in waste measurement, waste management and waste reduction. Nonetheless, individual hospitals and RACH foodservices remain responsible for driving change. There is an urgent need to improve food waste measuring practices in these Australian settings to achieve significant reductions in food waste.